Association of the G-protein and α2-adrenergic receptor gene and plasma norepinephrine level with clonidine improvement of the effects of diuretics in patients with cirrhosis with refractory ascites: a randomised clinical trial. Issue 11 (9th September 2010) - Yang, Y Y; Lin, H C; Lee, W P; Chu, C J; Lin, M W; Lee, F Y; Hou, M C; Jap, J S; Lee, S D
Abstract : Objective: Clonidine is an α2 -adrenoceptor agonist which, by coupling with G-protein, has been proposed as an alternative treatment for refractory ascites of patients with cirrhosis for several years. Genetic polymorphisms of β-adrenoceptor and angiotensin II type 1 receptor blockers have been reported to affect drug response in patients with cirrhosis. This study evaluated the clonidine–diuretic response rate, favourable predictors and genetic components of the clonidine–diuretic response in patients with cirrhosis with refractory ascites. Methods: 270 patients with cirrhosis with refractory ascites were randomised equally into two treatment groups to receive diuretics alone or the clonidine–diuretics association. The primary end point was clonidine–diuretic response rate. Secondary end points were mean daily dose of diuretics, times of paracentesis, ascites-related readmission and 1-year survival rate. Results: Good clonidine responders had better natriuresis and diuresis as well as a significant decrease in abdominal circumference, plasma renin, aldosterone and norepinephrine levels. The overall clonidine–diuretics response rate was 55–60%. In patients with cirrhosis, the prevalence of ARDA2 C WD/DD and GNB3 CT/TT genotypes was 71% and 77%, respectively. Among the responders, 71% of patients with cirrhosis had the ARDA2 C WD/DD genotype and 67% has the GNB3 CT/TT genotype. Besides higher baseline norepinephrine levels, the presence of both ARDA2 C WD/DD and GNB3 CT/TT genotypes showed a positive predictive value of 82% and a negative predictive value of 79% for good clonidine response. Conclusions: These results suggest that neurohormonal and genetic testing may be used as predictive factors for the additive effects of clonidine on the diuresis and natriuresis effects of diuretics in patients with cirrhosis with refractory ascites.